Characterization of CdTe+Mn crystals depending on doping procedure - Nikoniuk, E.S.; Zakharuk, Z.I.; Rarenko, I.M.; Kuchma, M.I.; Yurijchuk, I.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Electrophysical properties of CdTe+Mn crystals grown by three different doping scheme of manganese introduction were studied. It was found that the properties of the CdTe crystals doped with Mn strongly depend on both the initial manganese concentration and the doping procedure. Introduction of Mn in above-stoichiometric limit in concentration of C₀ < 10¹⁹ cm⁻³ gives n-type crystals. When manganese concentration is of C₀ >= 10¹⁹ cm⁻³ electron conductivity is not observed so as in the Cd₁₋xMnxTe solid solution crystals. A model explaining this phenomenon is proposed. Although manganese impurity in the CdTe crystals doesn't reveal any electrical activity it provides a formation of above-stoichiometric cadmium in electrically active positions Cdi and as a component of precipitates. An influence of above-stoichiometric cadmium is determined both by manganese concentration and by doping schemes, as well as by annealing and cooling temperature conditions of the doped samples.